Prevalence and determinants of HIV among reproductive-age women (15–49 years) in Africa from 2010 to 2019: a multilevel analysis of demographic and health survey data - Gedefie, Alemu; Muche, Amare; Mohammed, Anissa; Ayres, Aznamariam; Melak, Dagnachew; Abeje, Eyob Tilahun; Bayou, Fekade Demeke; Belege Getaneh, Fekadeselassie; Asmare, Lakew; Endawkie, Abel (Frontiers in Public Health, 2025)
BackgroundHuman immunodeficiency virus (HIV) remains the leading cause of global morbidity and mortality. The incidence of HIV is disproportionately higher in Sub-Saharan regions, particularly the Southern African sub-region, which is the most affected region and accounts for 77% of all new HIV infections in the region. Thus, the aim of this study was to identify the determinants of HIV among reproductive-age women in Africa.MethodsThis study was conducted among reproductive-age women in Africa, based on secondary data obtained from the Demographic Health Survey (DHS) conducted between 2010 and 2019. The outcome variable was HIV status, while individual- and community-level variables served as potential predictors. The model fit was assessed using Akaike’s Information Criterion, Bayesian Information Criterion, and − 2 Log likelihood. Then, multilevel mixed-effects analysis was used. Intra-cluster correlation coefficient, median odds ratio, and proportional change in variance were used to measure heterogeneity between clusters.ResultsA total of 292,810 unweighted and 293,773 weighted reproductive-age women in 26 African nations were included in this study. The overall prevalence of HIV among reproductive-age women in Africa was 4.34% (95% CI: 4.2, 4.4%). The highest percentage of HIV was found in Lesotho (23.98%), followed by South Africa (19.12%), and Mozambique (14.67%). However, the lowest HIV prevalence was found in Niger (0.54%), Senegal (0.59%), and Burundi (0.79%). Southern Africa has the highest HIV burden (18.5%), followed by Eastern Africa (6.1%), while Western African countries have the lowest HIV burden. Increasing maternal age, higher maternal education, women who were unemployed, a history of multiple sexual partners, women in a union, community-level educational status, community-level wealth index, African sub-region, and urban residence were found to be independent predictors of HIV infection in Africa.ConclusionThe burden of HIV has remained higher, highlighting the need for targeted public health intervention strategies to prevent the transmission of HIV among key populations.